TERPAAN BERITA LINGKUNGAN DAN RASA INGIN TAHU TENTANG ISU LINGKUNGAN SERTA PERILAKU PENOLAKAN PRODUK TIDAK RAMAH LINGKUNGAN - Sunu Probo Baskoro; Muhammad Zid; Samadi Samadi (Program Studi Manajemen Lingkungan, 2019)
This research is the research of korelasional consisting of two free variables and bound variables are one. Free variables in this study was exposure to Environmental News and curiosity over environmental issues, while the bound variable is the behavior for the rejection of products are not eco-friendly. The purpose of this research was to know is there a relationship between exposure to Environmental News with Rejection Behavior products are not eco-friendly, well know is the relationship between Curiosity over environmental issues with no Product Rejection Behavior Eco-friendly as well as the relationship of the second variable is free i.e. exposure to Environmental News and curiosity over environmental issues with Rejection Behavior products are not eco-friendly. Research carried out on Nationwide News Agency employee Among TV news coverage of Division in December 2018 until January 2019. Using the sample as many as 60 people were taken using a simple random sampling method, using the technique of data collection questionnaire and field observations. The research found that there is a positive relationship between exposure to Environmental News with Rejection Behavior products are not eco-friendly, in addition also found a positive relationship between Curiosity over environmental issues with Rejection Behavior Products are not eco-friendly. The second variable is free it also has a positive relationship with the behaviour of the rejection of products are not eco-friendly. When exposure to Environmental News and curiosity over environmental issues is improved then the behavior of the rejection of products are not eco-friendly.